Labour migration, human trafficking and multinational corporations : the commodification of illicit flows - Arhin, Antonela; Quayson, Ato (New York [etc.] Routledge, 2012)
Although much literature on human trafficking focuses on sex trafficking, a great deal of human trafficking results from migrant workers, compelled - by economic deprivation in their home countries - to seek better life opportunities abroad, especially in agriculture, construction and domestic work. Such labour migration is sometimes legal and well managed, but sometimes not so ? with migrant workers frequently threatened or coerced into entering debt bondage arrangements and ending up working in forced labour situations producing goods for illicit markets.
Keywords: Emigración e inmigración; Trabajadores extranjeros; Empresas multinacionales; Libros electrónicos